Inhibition of IGF-1R Prevents Ionizing Radiation-Induced Primary Endothelial Cell Senescence - Panganiban, Ronald Allan M.; Day, Regina M. (PLOS ONE, 2013)
Accelerated senescence is a primary response to cellular stresses including DNA damaging agents (e.g., ionizing radiation) and is widely believed to be caused by continuous proliferative signaling in the presence of cell cycle arrest. Studies of signal transduction pathways leading to accelerated senescence have revealed that inhibition of mammalian target of rapamycin (mTOR) by rapamycin rescues cells from senescence. However, the molecular mechanisms upstream of mTOR following ionizing radiation (IR) are not well defined. We investigated signal transduction leading to IR-induced accelerated senescence in human pulmonary artery endothelial cells (HPAEC). Exposure of HPAEC to X-rays (10 Gy, 2.4 Gy/min) upregulated senescence markers including p53, p21/waf1, and senescence-associated beta galactosidase (SA-β-gal). Ly294002 (a phosphatidylinositol-3-kinase [PI3K] inhibitor) or rapamycin (an mTOR inhibitor) blocked the induction of cellular senescence markers suggesting roles for PI3K and mTOR. Pathway-directed microarrays revealed increased transcription of insulin-like growth factor I (IGF-1), a modulator of cell growth and proliferation upstream of mTOR. qRT-PCR confirmed that both IGF-1 and IGF-2 mRNA were increased in response to X-rays, and ELISA showed increased secretion of IGF-1 protein into the medium of irradiated HPAEC. Consistent with upregulation of these ligands, we found that X-ray exposure led to hyperphosphorylation of IGF-1R, the receptor for IGF-1 and -2. Treatment with AG1024, an IGF-1R inhibitor, suppressed IR-induced upregulation of p53, p21/waf1, and SA-β-gal. Together these findings suggest that IGF-1R is a key regulator of IR-induced accelerated senescence in a pathway that requires intact mTOR activity upstream of both p53 and p21/waf1.